Enhancing Maize Production Through Timely Nutrient Supply: The Role of Foliar Fertiliser Application - Brian Ssemugenze; Akasairi Ocwa; Ronald Kuunya; Costa Gumisiriya; Csaba Bojtor; János Nagy; Adrienn Széles; Árpád Illés (Agronomy)
Maize, regarded as a staple economic crop, attracts special global attention with the aim to enhance its production. Foliar fertilisation offers a complementary method to traditional soil fertilisation amongst resource-limited agricultural systems, providing a more efficient solution to nutrient deficiencies, especially in suboptimal soil conditions. This study aimed to analyse foliar fertiliser formulation research directions and their application in maize production. A literature search was conducted in the Web of Science (WoS) database. Bibliometric analyses were performed using the VOSviewer software (version 1.6.17). The changes in the publication trends of documents were tested using the Mann–Kendall test. The production effects of foliar fertilisation were independently synthesised. The results showed a strong positive increase in publication trends regarding maize foliar fertilisation (R2 = 0.7842). The predominant nutrients that affected maize production were nitrogen, phosphorous, potassium, zinc, iron, and manganese. The timely foliar application of nutrients corrected deficiencies and/or sustained nutrient supply under several abiotic stresses. Foliar application at critical growth stages like flowering and grain filling boosted carbohydrate and protein content, lipid levels, kernel size, mineral content, and the weight of the maize grain. This review identified important research gaps, namely genotype-specific responses, interactions with other agronomic practices, and long-term environmental effects.